2003
DOI: 10.1080/00015458.2003.11679502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesh and its Localisation on Testicular Flow and Spermatogenesis in Patients with Groin Hernia

Abstract: In this study, the long-term effects of mesh and its localisation (i.e. anterior or posterior) on testicular perfusion and testicular function were evaluated in groin hernia patients. Testicular function has been evaluated with spermiogram and testicular perfusion with colour Doppler ultrasonography. Group I: consisted of 30 posterior preperitoneal mesh repair patients Group II: consisted of 30 anterior tension-free repair patients. The operation types were randomised with a systematic sampling method. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…This difference had disappeared by the time of the subsequent examination (sixth month), and this was attributed to the trauma of the operation and to tissue edema 16 . These authors did not consider the possibility that these alterations might have occurred because of the inflammatory reaction triggered by the prosthesis.…”
Section: Analysis Of the Testicular Flowmentioning
confidence: 97%
See 3 more Smart Citations
“…This difference had disappeared by the time of the subsequent examination (sixth month), and this was attributed to the trauma of the operation and to tissue edema 16 . These authors did not consider the possibility that these alterations might have occurred because of the inflammatory reaction triggered by the prosthesis.…”
Section: Analysis Of the Testicular Flowmentioning
confidence: 97%
“…This was not what was seen in the present study. Aydede et al 16 observed a decreased *TV = Testicular Volume; SV = Systolic Velocity; DV = Diastolic Velocity; RI = Resistance Index; PI = Pulsatility Index.…”
Section: Analysis Of the Testicular Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast others have found proximal dilatation but no thickening of the wall of the vas deferens 2 . Decreased arterial perfusion in the testis 5,7 and spermatic venous thrombosis 4 have also been reported.. One study has shown beneficial effects on the integrity of the vas deferens when using lightweight mesh 3 whereas another study did not find any difference in inflammation and fibrosis comparing heavyweight with lightweight mesh 8 .…”
Section: Introductionmentioning
confidence: 99%